Facile electro-thermal igniters based on freestanding CNTs films for the ignition of energetic materials. (1st December 2022) - Kang, Xiaoli; Li, Chunhong; Cui, Wen; Yuan, Hao; Wang, Zhengshang; Zheng, Zhou; Cui, Xudong
Abstract: Facile electro-thermal igniters based on freestanding carbon nanotubes (CNTs) films are investigated for exploring the use of igniting energetic materials. Increases in electro-thermal temperature, dynamic pictures of ignition process, and temporal changes of voltage, current and resistance as well as the ignition ability of freestanding CNTs film–based igniters with different film thickness are compared with their counterparts with paper-like substrate. The results demonstrated that freestanding CNTs film–based igniters had faster rise in electro-thermal temperature and better ignition ability than their counterparts. The ignition delay of loaded energetic materials employing freestanding CNTs film based–igniters was only 40%–67% of their counterparts depending on the film thickness. Freestanding CNTs film–based igniters with larger thicknesses were more suitable for the rapid ignition of energetic materials. The shortest ignition delay for igniters of 8 × 8 mm bridge area under 20 V was less than 80 ms. The initial temperature rise rate of igniters was crucial for deciding the ignition delays of loaded energetic materials. The presence of substrates in CNTs film–based igniters impeded their temperature rise rate and thus increased the ignition delay of loaded energetic materials. Moreover, due to the property of negative resistance-temperature coefficient, freestanding CNTs film–based igniters are favourable for the realization of low voltage ignition of energetic materials.